1999
DOI: 10.1037/0022-3514.77.5.979
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stereotype-incongruent information on perceived group variability and stereotype change.

Abstract: Three experiments showed increases in the perceived variability of social groups after perceivers received stereotype-incongruent information about group members. In Experiment 1, participants generated flatter distributions after exposure to incongruent information, compared with equally deviant congruent information, in the form of typical verbal materials. Experiment 2 indicated similar changes in dispersion after the presentation of numeric information about a single group member. In Experiment 3, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 37 publications
2
43
1
1
Order By: Relevance
“…Incongruent exemplars were perceived in the present studies as less typical than congruent or supercongruent exemplars, but the data does not support the idea of a mediation by perceived typicality (see 10.2). Consistent with previous research, Study 5 showed a tendency that incongruent exemplars lead to a less homogenous picture of the group (Garcia-Marques & Mackie, 1999;Paolini et al, 2004). The lack of impact of incongruent information on the stereotype obtained ion the present studies is inconsistent with the inclusion/exclusion model (Schwarz & Bless, 1992;, which regards assimilation as the default process when dealing with exemplar information.…”
Section: Results In Light Of Previous Findings and Theoriescontrasting
confidence: 50%
See 2 more Smart Citations
“…Incongruent exemplars were perceived in the present studies as less typical than congruent or supercongruent exemplars, but the data does not support the idea of a mediation by perceived typicality (see 10.2). Consistent with previous research, Study 5 showed a tendency that incongruent exemplars lead to a less homogenous picture of the group (Garcia-Marques & Mackie, 1999;Paolini et al, 2004). The lack of impact of incongruent information on the stereotype obtained ion the present studies is inconsistent with the inclusion/exclusion model (Schwarz & Bless, 1992;, which regards assimilation as the default process when dealing with exemplar information.…”
Section: Results In Light Of Previous Findings and Theoriescontrasting
confidence: 50%
“…A rather heterogeneous group of researchers (some allude to prototype models, others to exemplar models) assumes that the variability components of stereotypes do change, whereas other aspects remain stable (e.g., Garcia-Marques & Mackie, 1999;Hamburger, 1994;Paolini, Hewstone, Rubin, & Pay, 2004). The topic of stereotype change will be covered in more detail in chapter 4.…”
Section: Stereotypes: How Are They Represented?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ferreira et al 2006;Garcia-Marques, Hamilton and Maddox 2002;Garcia-Marques and Mackie 1999;. In fact, this paradigm has been among the most cited topics in social psychology in other European countries and the United States since the 1990s, but has only in recent years become the target of an increasing attention in Portugal.…”
Section: Topicmentioning
confidence: 99%
“…After encountering instances with unexpected properties can we conclude that the typical properties (e.g., average value) of a category (e.g., stocks) have changed? It seems evident that in order to remain useful, knowledge and beliefs about category properties need to reflect changes in underlying category structure (Garcia-Marques & Mackie, 1999). The challenge for a perceiver is to determine when meaningful change has actually occurred and to be able to differentiate this from the case when exemplar deviation simply arises from natural variability around the category central tendency.…”
Section: Introductionmentioning
confidence: 99%